Synthesis, self-assembly, and air-stable radical anions of unconventional 6, 7-bis-nitrated N-annulated perylene diimides. Issue 7 (8th July 2020) - Cann, Jonathan; Gelfand, Benjamin Sidney; Welch, Gregory C.
Abstract : Unusual 6, 7-bis-nitrated N -annulated perylene diimides are reported which have stabilized frontier molecular orbitals. The highly stabilized LUMO enables the generation of air-stable radical anions. Abstract : Unusual 6, 7-bis-nitrated N -annulated perylene diimides are reported which have stabilized frontier molecular orbitals making them highly electron deficient. Radical anion formation under ambient conditions is readily feasible. A crowded NO2 substitution pattern significantly alters the perylene core geometry. Varied functionalization at the pyrrolic N-position allows for crystal engineering.